DIRECT REPORTED SPEECH IN SPOKEN INDONESIAN: VERBAL MARKERS AND DISCOURSE PRACTICES - Juliana Wijaya (Masyarakat Linguistik Indonesia, 2016)
The analysis of first, second and third-person reported speech in this paper reveal different uses of verbal markers and discourse practices surrounding direct reported speech in spoken Indonesian. The reporting verb and noun phrases bilang ‘to say,’ ngomong ‘to talk,’ and katanya ‘his/her word’ are the most frequently used. The moodinvoking reporting verbal markers are not frequently used in conversational Indonesian. Speech-signalling reporting verbs embody illocutionary forces and presuppose the performative modality of the projected reported speech. Furthermore, speakers of reported speech use different strategies to introduce or mark quoted speakers. Some of them are not specifically marked yet their existence can be interpreted by taking the underlying operations of the turn taking system into account.